2022
DOI: 10.1002/agm2.12235
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderic Acid A targeting leucine‐rich repeat kinase 2 involved in Parkinson's disease–A computational study

Abstract: BackgroundParkinson's disease (PD) is the second most common neurodegenerative disorder after Alzheimer's disease (AD). The exact mechanism behind PD disease is still unknown and PD is marked by symptoms like bradikynesia, tremors, walking or gait difficulties, etc. The current medication used for PD is levodopa, and researchers are trying to develop a promising drug for PD. In our study, we took Ganodema lucidium mushroom, known as “Reishi mushroom,” which has antioxidant, antiinflammatory, antihepatic proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This combined effect may arise from the preservation of mitochondrial functional integrity [ 16 ]. The molecular dynamics simulation results also indicated that ganoderic acid A has the potential to effectively target Leucine-rich repeat kinase 2 (LRRK2) [ 17 ]. LRRK2 is strongly associated with neurological illnesses, particularly PD, as certain genetic variations in this gene have been found to increase susceptibility to PD.…”
Section: Discussionmentioning
confidence: 99%
“…This combined effect may arise from the preservation of mitochondrial functional integrity [ 16 ]. The molecular dynamics simulation results also indicated that ganoderic acid A has the potential to effectively target Leucine-rich repeat kinase 2 (LRRK2) [ 17 ]. LRRK2 is strongly associated with neurological illnesses, particularly PD, as certain genetic variations in this gene have been found to increase susceptibility to PD.…”
Section: Discussionmentioning
confidence: 99%
“…The overall sum between all these variables was calculated in one variable known as ΔGbind. Further, the parameters such as ΔG covalent , ΔG couloumb , and ΔG vdW were also calculated using the MM-GBSA module of the Schrodinger suite 2022 [20]. The compound JD-7 was found to have the highest binding score (− 7.94 kcal/mol) with the 4FVT, among all the designed quinoline derivatives.…”
Section: Molecular Mechanics-generalized Born Surface Area Studies (M...mentioning
confidence: 99%
“…Ganoderic acid A (GAA) represents the most thoroughly researched among ganoderic acids derived from Ganoderma lucidum due to its effects against NDDs. For example, Ahmad et al [ 74 ] investigated the potential of GAA against PD through a computational analysis involving ADMET analysis, molecular docking, molecular dynamics simulations, and MMGBSA calculations. Focused on the leucine-rich repeat kinase 2 (LRRK2), a key protein implicated in PD, the study concluded that GAA exhibited promising therapeutic effects necessitating further in vitro and in vivo validation.…”
Section: Potential Active Compounds From Ganoderma Lucidum ...mentioning
confidence: 99%